COPING WITH PRAYING SUPPORTS: INDONESIAN MUSLIM RESPONSE TO THE PANDEMIC - Ruslan Sangaji (IAIN Bone, 2022)
Abstract: The purpose of this study is to explore the prayers of the Indonesian Muslim community at various levels to deal with COVID-19. An analysis of the reasons why prayer is important at every level of society is described here. This study presents three levels of support for the prayers of the Indonesian people in dealing with COVID-19, namely the structural level, cultural level and personal level. Descriptive qualitative method is used in this study which is based on data and information sourced from online news. Data were collected, then processed, and then analyzed using a hermeneutic approach. The findings of this study show that prayer support at every level of society as a spiritual solution in dealing with the COVID-19 pandemic is a coping with religious values which is considered more important to support solutions and other ways. Concepts in Islam have taught people about the factors that cause disasters and how to respond to them. Therefore, the Indonesian people view COVID-19 as a disaster and a provision from God. At the same time it is also judged as a consequence of the consequences of human actions. Community prayer support that is carried out collectively has an impact on spiritual strengthening which affects the soul and mentality of the community. Spiritual strengthening is also determined by belief and awareness of one's religious teachings.